2020
DOI: 10.5751/ace-01540-150112
|View full text |Cite
|
Sign up to set email alerts
|

A multiscale analysis of Gray Vireo (Vireo vicinior) nest-site selection in central New Mexico

Abstract: There are many gaps in our understanding of Gray Vireo (Vireo vicinior) life history especially as it relates to nesting ecology. Our objective was to determine habitat features selected by Gray Vireos for nesting to improve management strategies for breeding populations. We searched for Gray Vireo nests on Kirtland Air Force Base in Albuquerque, New Mexico from 2016 to 2017. We estimated Gray Vireo nest-site selection at the tree level, the surrounding vegetation, and at two broader scales corresponding to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Additionally, our data suggested that optimum juniper density for nest survival was 15–20% of the available cover; however, the confidence intervals for this relationship overlapped with zero. It is interesting to note, however, that this percentage of juniper cover is similar to optimum juniper density for gray vireo nest-site selection ( Harris, Smith & McMurry, 2020 ).…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…Additionally, our data suggested that optimum juniper density for nest survival was 15–20% of the available cover; however, the confidence intervals for this relationship overlapped with zero. It is interesting to note, however, that this percentage of juniper cover is similar to optimum juniper density for gray vireo nest-site selection ( Harris, Smith & McMurry, 2020 ).…”
Section: Discussionmentioning
confidence: 76%
“…Elevations at random locations ranged from 1823–2148 m. Surveys were conducted at the same random points each year. At each point, we conducted a 10-min survey consisting of 4 min of passive surveying, followed by 1 min of broadcast of conspecific vocalizations from a portable speaker (Cass Creek Big Horn), followed by 5 min of passive surveying ( Harris, Smith & McMurry, 2020 ). Broadcasts were of an adult male Gray Vireo song from the Arizona Field Ornithologist Sound Library and were played at maximum volume.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations